Salidroside may target PPARα to exert preventive and therapeutic activities on NASH - Chu, Xueru; Liu, Shousheng; Qu, Baozhen; Xin, Yongning; Lu, Linlin (Frontiers in Pharmacology, 2024)
Background: Salidroside (SDS), a phenylpropanoid glycoside, is an antioxidant component isolated from the traditional Chinese medicine Rhodiola rosea and has multifunctional bioactivities, particularly possessing potent hepatoprotective function. Nonalcoholic steatohepatitis (NASH) is one of the most prevalent chronic liver diseases worldwide, but it still lacks efficacy drugs. This study aimed to assess the preventive and therapeutic effects of SDS on NASH and its underlying mechanisms in the mice model subjected to the Methionine-and Choline-Deficient (MCD) diet. Methods: C57BL/6J mice were fed with an MCD diet to induce the NASH model. During or after the formation of the MCD-induced NASH model, SDS (24 mg/kg/day) was dietary supplied for four weeks. The histopathological changes were evaluated by H&E staining. Oil red O staining and Sirius red staining were used to quantitatively determine the lipid accumulation and collagen fibers in the liver. Serum lipid and liver enzyme levels were measured. Morphology of autophagic vesicles and autophagosomes was observed by TEM, and the qRT-PCR and western blotting were used to detect autophagy-related factor levels. Immunohistochemistry and TUNEL staining were used to evaluate the apoptosis of liver tissues. Flow Cytometry was used to detect the composition of immune cells. ELISA was used to evaluate the expression of serum inflammatory factors. The transcript-proteome sequencing, molecular docking, qRT-PCR and western blot were performed to explore the mechanism and the target of SDS on NASH. Results: The oral administration of SDS demonstrated comprehensive efficacy in NASH. SDS showed both promising preventive and therapeutic activity on NASH in vivo. SDS could up-regulate autophagy, down-regulate apoptosis, rebalance immunity, and alleviate inflammation to exert anti-NASH properties. Finally, as the results of transcript-proteome sequencing, molecular docking evaluation and experimental validation, SDS might exert its multiple effects through targeting PPARα.Conclusions: Our findings revealed that SDS could regulate liver autophagy and apoptosis, regulating both innate immune and adaptive immune, alleviating inflammation in NASH prevention and therapy via the PPAR pathway, suggesting that SDS could be a potential anti-NASH drug in the promising future.